1999
DOI: 10.1038/sj.bjc.6690144
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity at 18q21 is indicative of recurrence and therefore poor prognosis in a subset of colorectal cancers

Abstract: Summary Adjuvant therapies are increasingly used in colorectal cancers for the prevention of recurrence. These therapies have side-effects and should, thus, be used only if really beneficial. However, the development of recurrence cannot be predicted reliably at the moment of diagnosis, and targeting of adjuvant therapies is thus based only on the primary stage of the cancer. Loss of heterozygosity (LOH) in the long arm of chromosome 18 is suggested to be related to poor survival and possibly to the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 26 publications
3
26
0
1
Order By: Relevance
“…A number of studies have investigated the use of various combinations of molecular markers to predict clinical outcome in the hope that these may help to identify high-risk patients and hence enable appropriate neoadjuvant and/or adjuvant treatment. [27][28][29][30] In the present study, we showed that increased preoperative circulating VEGF levels were significantly correlated with tumor size, and nodal and distant metastases, which are well known prognostic factors. VEGF is a multifunctional cytokine that increases microvascular permeability and directly stimulates endothelial cell growth and angiogenesis, and many VEGF concentrations are an independent risk factor for colorectal tumor recurrence.…”
Section: Discussionmentioning
confidence: 56%
“…A number of studies have investigated the use of various combinations of molecular markers to predict clinical outcome in the hope that these may help to identify high-risk patients and hence enable appropriate neoadjuvant and/or adjuvant treatment. [27][28][29][30] In the present study, we showed that increased preoperative circulating VEGF levels were significantly correlated with tumor size, and nodal and distant metastases, which are well known prognostic factors. VEGF is a multifunctional cytokine that increases microvascular permeability and directly stimulates endothelial cell growth and angiogenesis, and many VEGF concentrations are an independent risk factor for colorectal tumor recurrence.…”
Section: Discussionmentioning
confidence: 56%
“…Loss of heterozygosity (LOH) is one of the major types of genetic inactivation, and the long arm of chromosome 18 is the most frequently deleted region in colorectal cancers. To date, many reports suggest that this deletion is a molecular predictor that affects survival (Fearon et al, 1990;Jen et al, 1994;Chung, 1998;Lanza et al, 1998;Ogunbiyi et al, 1998;Jernvall et al, 1999;McLeod and Murray, 1999;Sarli et al, 2004). We too reported that the allelic deletion of chromosome 18q was associated with poorer prognosis in stage III colon cancer after adjuvant chemotherapy (Watanabe et al, 2001.…”
mentioning
confidence: 77%
“…In HCC, 18q is lost in 10 ± 20% of the cases, with a higher frequency in advanced tumors (Kato et al, 1998). In colorectal and head and neck carcinomas, loss of 18q represents a poor prognostic marker (Jernvall et al, 1999;Pearlstein et al, 1998). In addition, the 18p11 region has been reported to contain at least two potential tumor suppressor genes implicated in lung, brain and possibly in breast cancer (Tran et al, 1998).…”
Section: Fibrolamellar Carcinomamentioning
confidence: 99%